Effect of in-seat exercising on comfort perception of airplane passengers. (November 2018) - Bouwens, Joyce M.A.; Fasulo, Luisa; Hiemstra-van Mastrigt, Suzanne; Schultheis, Udo W.; Naddeo, Alessandro; Vink, Peter
Abstract: Sitting still for extended periods of time can lead to physical discomfort and even serious health risks. Due to safety regulations, reducing passenger' sitting time in aircrafts is not feasible. This paper presents the results of a laboratory study, in where an interactive airplane seat was compared with a current economy class seat. Participants used both seats for 3.5 h, and performed significantly more in-seat movements when using the interactive seating system. Furthermore, this interactive seat predominantly lead to significantly better comfort experiences and reduced discomfort experiences, however no significant differences have been found in self-reported localized musculoskeletal discomfort. Passengers indicated that they would prefer this interactive seat over a standard aircraft seat. Highlights: Passengers move significantly more when using the interactive seating system. Significantly better comfort was reported after using the interactive seating system. Airplane passengers prefer the interactive seating system over a regular seat.